How individual scores affect the final expert-based assessments of ecosystem services: Range and mean scores analysis of natural heritage supply maps - Hristina Prodanova; Desislava Varadzhakova (European Journal of Geography)
Ecosystems representing the Natural Heritage (NH) are considered in this study as an important source of ecosystem goods and services for human well-being. On that spatial base, we conducted an expert-based assessment and mapping of their potential to provide ecosystem services (ES) for recreational purposes in Bulgaria. Twelve experts participated in the expert-based assessment by filling individual matrices for the potential of the NH to provide ES. We analysed the results i.e. individual scores by comparing them, and calculating the minimum, the maximum and the range scores between them. We calculated the mean individual experts’ scores by ecosystem types and subtypes for nine prioritized ecosystem services for recreation – 2 provisioning, 2 regulating and 5 cultural. The results show that individual experts have different perceptions for some ecosystems and their services due to their different scientific expertise. This follows from the quite high ranges i.e., 4 or 5 units between maximum and minimum score per spatial unit. There are: (i) significant variations in scoring of Grasslands, Wetlands, Croplands, Rivers and lakes, and Urban ecosystems; and (ii) considerable similarities about Woodland and forest, Sparsely vegetated lands and Marine ecosystems. To compare the spatial discrepancies between the experts’ scores, we map them individually. A final integrated map represents the potential of the NH in Bulgaria to provide ecosystem services for recreation with an average score above 3.00. The main outcomes of our study are the analyses we made on the individual and the group experts’ scores.